ILLUMINATING STUDENTS’ UNDERSTANDING AND ACCEPTANCE TOWARDS THE DUAL LANGUAGE PROGRAMME (DLP) - Ashairi Suliman; Mohamed Yusoff Mohd Nor; Melor Md Yunus (Jurnal Cakrawala Pendidikan, 2020)
The Dual Language Programme (DLP) is an initiative introduced by the Ministry of Education to advocate the teaching and learning of science and mathematics in the English language. Resembling the previous educational policy named PPSMI, this programme commenced in 2016, offering the flexibility for English to be used as the instructional medium for the two subjects. After four years of its inception, it is crucial to discover the programme's acceptance among those involved directly with the programme. Thus, this study expounds students’ understanding and acceptance of the programme by investigating the influence of age, gender, locality and the type of school on their understanding and acceptance of DLP.   This study involved 2162 students, and it was found that their understanding and acceptance level of the programme are at a moderately high level. The findings also revealed a significant difference between the acceptance of the programme. As an alternative to solidify the English mastery, the implementation of DLP needs to be improved for it to be well-accepted by interest groups.